2020
DOI: 10.1038/s41467-020-19905-4
|View full text |Cite
|
Sign up to set email alerts
|

A mechanically adaptive hydrogel with a reconfigurable network consisting entirely of inorganic nanosheets and water

Abstract: Although various biomimetic soft materials that display structural hierarchies and stimuli responsiveness have been developed from organic materials, the creation of their counterparts consisting entirely of inorganic materials presents an attractive challenge, as the properties of such materials generally differ from those of living organisms. Here, we have developed a hydrogel consisting of inorganic nanosheets (14 wt%) and water (86 wt%) that undergoes thermally induced reversible and abrupt changes in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Electrostatic interactions are abundant in biological complexes and represent an efficient strategy to generate ionic complexes, mediate biomolecular attachment, and stabilize molecular conformation to prolong biomolecular activities. This strategy has recently received increasing attention for the construction of dynamic hydrogels for various biomedical applications. For example, alginate, a natural anionic polymer derived from kelps, has been widely used for biomedical applications including wound healing, tissue engineering, and drug/protein delivery . The structure of the alginate molecule allows strong ionic interactions and a high degree of coordination with di- or trivalent ions, resulting in the formation of ionically cross-linked dynamic hydrogels.…”
Section: Properties and Fabrication Approaches For Dynamic Hydrogelsmentioning
confidence: 99%
“…Electrostatic interactions are abundant in biological complexes and represent an efficient strategy to generate ionic complexes, mediate biomolecular attachment, and stabilize molecular conformation to prolong biomolecular activities. This strategy has recently received increasing attention for the construction of dynamic hydrogels for various biomedical applications. For example, alginate, a natural anionic polymer derived from kelps, has been widely used for biomedical applications including wound healing, tissue engineering, and drug/protein delivery . The structure of the alginate molecule allows strong ionic interactions and a high degree of coordination with di- or trivalent ions, resulting in the formation of ionically cross-linked dynamic hydrogels.…”
Section: Properties and Fabrication Approaches For Dynamic Hydrogelsmentioning
confidence: 99%
“…[ 1–4 ] For example, stiffness‐changing materials offer dynamic shape adaptability and load‐bearing capability. [ 5–7 ] In nature, stiffness‐changing behavior is essential for living organisms to better adapt to various conditions. [ 8–11 ] Environmental pressures and predator–prey relationships have driven organisms to evolve with tissue structures that can change to regulate their body's mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Differing from living organisms containing water-rich pliable solids that are in response to external stimuli or adaptive to applied mechanical forces, inorganic constituents usually do not possess comparable flexibility, processability and responsiveness. 11 In this work, on the basis of their pH-controlled protonation/ deprotonation and thermally responsive hydrogen bonding we showed that the 2D GO sheets can serve as an alternative to 1D polymers or organic nanofibers in constructing smart biomimetic soft matter with high water content, by means of a high-speed centrifugation-induced gelation. The advantages of employing the GO gelator as building blocks include its commercial availability, good biocompatibility, and biodegrad-ability.…”
Section: T H Imentioning
confidence: 80%
“…10,22−25 A pioneering work by Sano et al has reported a biomimetic hydrogel with mechanical adaptivity and thermal responsiveness from synthetic titanate nanosheets and water. 11 Here, we demonstrated that an inorganic hydrogel can be fabricated to be dually responsive, both mechanically and tribologically adaptive, and highly lubricative simply using commercially available GO nanosheets and water. The pH-and thermal responsiveness could play a synergistic role in controlling the gel properties and led to a more dramatic switch in the mechanical elasticity and friction.…”
Section: T H Imentioning
confidence: 91%